The killing. The complete fourth season [videorecording (DVD)] - Enos, Mireille, 1975-; Kinnaman, Joel, 1979-; Campbell, William, 1959-
"Following the shocking murder of her former lover, detective Sarah Linden (Mireille Enos) joins her partner Stephen Holder (Joel Kinnaman) in a race to destroy evidence that would implicate Linden in the crime. Meanwhile, the two must resolve a case involving the horrifying slaying of a prominent family whose son is enrolled in a respected military academy."-- Container.